Luciculio, a new genus with nine new species from Limpopo and Mpumalanga in South Africa (Coleoptera: Curculionidae: Entiminae: Embrithini) - Borovec, Roman (Zootaxa, 2022)
A new genus Luciculio gen. n., belonging to the tribe Embrithini Marshall, 1942 of the curculionid subfamily Entiminae, is described. It includes nine new species, all from the northeastern part of South Africa: Luciculio venda spec. n., type species, L. albuscrocodilus spec. n., L. ramabulanai spec. n., L. rudyardi spec. n., L. schoemani spec. n., L. soutpansbergensis spec. n., L. thathevondoensis spec. n., L. thohoi spec. n. and L. vhuvha spec. n. All species are illustrated and keyed.